Ler televisão limites do curso tv na escola e os desafios de hoje em Sergipe - Rocha, Florisvaldo Silva (2008)
In Reading Television: Limits of the course TV in the School and the Challenges of Today in Sergipe , we had as objective to detect that type of critical reading of the cultural texts produced by the television, professionals of the education of the public net of the basic and average education of the state of Sergipe that all had concluded its 3 (three) modules carries through. We were effectively tutorial of the first edition of this course of extension in the distance and witness some inconsistencies in its application, moment where the instigated investigation appeared: ahead of the current necessity of if understanding with a critical sense, the paper that plays it measured them in orchestration of the globalizado world, that type of critical reading of the audiovisual language is capable to carry through a professional of the education that participated of a course of this nature? Beginning with documental analysys and qualitative metodology we try to analyse in four chapters, since the origins and motivations of this course, to the opinions of 10 (ten) former course students about the approaches of the same thematic subject by two different television new programs, without missing the opinions of the tutors about the conditions in which were made 4 (four) consecutive editions of the course in Sergipe nor the concrete relationships estabilished by the former course students and the audiovisual on their everyday routine both at home and at work. We conclude that the reading made by the former course students is based on common sense and then not satisfactory to the requirements of this task nowadays, and at the same time we point out that the course failed, for it presented severe issues in terms of management and operations in its practical application to distance, by priorizing quantity over quality, by linking itself to a deficient technical structure, by not beholding the diosyncrasies nor the fundamental videos the teachers have access everyday and that it all had direct relation with the attachment of this course to a verticalized policy of technologization of brazilian education.